2021
DOI: 10.1111/auar.12347
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Social Responsibility Enhance Financial Performance? Evidence from Australia

Abstract: Despite the heightened interest in corporate social responsibility (CSR) in recent years, the question of whether CSR affects a firm's financial performance remains unresolved. Using a sample of Australian publicly listed firms over the period 2009–2015, we find that CSR enhances financial performance. The positive relationship is more pronounced in mining firms than it is in non‐mining firms. However, the financial benefit of CSR is negatively moderated by the level of industry competition. These empirical fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 88 publications
(141 reference statements)
2
15
0
3
Order By: Relevance
“…Some researchers subscribe to Friedman's view on CSR and suggest that corporate social practices take away the managers' attention and corporate resources to maximize economic profits, hence decreasing financial performance (Friedman, 2007). Other researchers have argued that corporate social practices are aligning corporate practices with multiple stakeholders' expectations and will elicit stakeholders' positive responses, hence enhancing the likelihood CCSM 30,3 of gaining success in financial performance (G omez-Bezares et al, 2017;Nguyen et al, 2022;Rodriguez-Fernandez, 2016). Yet, some studies have reported null results between corporate social performance and corporate financial performance (Zhao and Murrell, 2016).…”
Section: Voluntary Sustainability Reporting and Financial Performancesmentioning
confidence: 99%
“…Some researchers subscribe to Friedman's view on CSR and suggest that corporate social practices take away the managers' attention and corporate resources to maximize economic profits, hence decreasing financial performance (Friedman, 2007). Other researchers have argued that corporate social practices are aligning corporate practices with multiple stakeholders' expectations and will elicit stakeholders' positive responses, hence enhancing the likelihood CCSM 30,3 of gaining success in financial performance (G omez-Bezares et al, 2017;Nguyen et al, 2022;Rodriguez-Fernandez, 2016). Yet, some studies have reported null results between corporate social performance and corporate financial performance (Zhao and Murrell, 2016).…”
Section: Voluntary Sustainability Reporting and Financial Performancesmentioning
confidence: 99%
“…CSR disclosure can help to build an organisation's reputation for social responsibility (Ioannou and Serafeim 2016;Bianchi et al 2019;Nguyen et al 2021) and corporations can compete for capital (MacKey et al 2007) and for customers (Lee and Lee 2015;Bianchi et al 2019) based on their reputation for socially responsible activities. Lee and Lee (2015) distinguish between an organisation's minimal economic and legal standards (somewhat like meeting the minimum legitimacy threshold) and more exacting ethical and philanthropic standards.…”
Section: Corporate Culture/reputation Perspectivementioning
confidence: 99%
“…2019; Nguyen et al. 2021) and corporations can compete for capital (MacKey et al. 2007) and for customers (Lee and Lee 2015; Bianchi et al.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…We should encourage industrial restructuring and energy structure optimization and further promote low-carbon city policies, which will benefit both shareholders and the whole society in the long term. 38,[50][51]…”
Section: Underlying Mechanismsmentioning
confidence: 99%